KOMPOSISI ARTHROPODA PERMUKAAN TANAH DI KAWASAN PENAMBANGAN BATUBARA DI KECAMATAN TALAWI SAWAHLUNTO - Nurhadi, Nurhadi; widiana, Rina (Sainstek : Jurnal Sains dan Teknologi, 2010)
The research has been done to test the arthropod composition of surface soil at coal mining territory in Talawi district. The arthropod samples were taken by pitfall traps (totally 30 pitfall traps) in three different areas. At the first stage, the soil temperature was measured in the field. At the next stage, the soil chemists such as pH, humidity and soil organic, were analyzed in the laboratory. At the area I, the surface soil arthropods collected were from 9 ordo, 26 families, 31 species, and 3609 individuals. Meanwhile at the area II, the arthropods were 12 ordo, 26 families, 31 species, and 2502 individuals. At the last area, the arthropods collected were 12 ordo, 25 families, 28 species and 1272 individuals. Finally, it can be summarized that the arthropod composition on the three surface soils was similar with the similarity index 55.7%. It means the chemical and physical factors of the three areas still optimally supported the surface soil arthropods life cycle.Key words: surface soil, arthropods, composition, coal mining